Causal impact price transmission of the rice markets in Thailand - Wanvilai Chulaphan (2018)
This paper analyses the causal impact price transmission among four different market levels of Thai rice over the period of 2001 to 2009. A co-integration analysis reveals that a long-run equilibrium relationship exists among farm gate, wholesale, retail, and export prices. Furthermore, significant upstream and downstream causal relationships are identified based on Granger causality test. These results together with the Wald (X2) coefficient test confirm that changes in farm gate prices provided the largest effect to export and wholesale prices, respectively. Consequently, exports are at a disadvantage when producer-oriented policies are launched.